2001
DOI: 10.1076/opep.8.4.237.1613
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cardiovascular disease and its risk factors with age-related macular degeneration: the POLA study

Abstract: The POLA study (June 1995 through July 1997) is a population-based study on cataract and age-related macular degeneration (AMD) and their risk factors in 2584 residents of Séte (South of France), aged 60--95 years. Classification of AMD was performed on 50 degrees fundus photographs, according to an international classification. The presence of cardiovascular disease and its risk factors was determined by interviewer-based questionnaire, clinical examination (anthropometry, blood pressure) and fasting plasma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
145
6
9

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 218 publications
(168 citation statements)
references
References 22 publications
8
145
6
9
Order By: Relevance
“…Meanwhile, the Pathologies Oculaires Liees a l'Age (POLA) study in France demonstrated an increased risk of advanced AMD and pigmentary abnormalities in obese participants. (18) In the AREDS study significant associations between greater BMI, neovascular AMD and geographic atrophy were observed. (4,19) In sum these findings contribute to the body of evidence that overweight/obesity and markers of obesity are associated with AMD, possibly through an increase in oxidative damage and inflammation in overweight/obese persons (11).…”
Section: Body Mass Index and Markers Of Obesitymentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, the Pathologies Oculaires Liees a l'Age (POLA) study in France demonstrated an increased risk of advanced AMD and pigmentary abnormalities in obese participants. (18) In the AREDS study significant associations between greater BMI, neovascular AMD and geographic atrophy were observed. (4,19) In sum these findings contribute to the body of evidence that overweight/obesity and markers of obesity are associated with AMD, possibly through an increase in oxidative damage and inflammation in overweight/obese persons (11).…”
Section: Body Mass Index and Markers Of Obesitymentioning
confidence: 99%
“…The relationship between BMI and AMD has been previously studied (4,11,(16)(17)(18)(19). The Beaver Dam Eye Study (BDES) showed a significant relationship between higher BMI, higher waistto-hip ratio and early AMD in women, (16) while the Blue Mountains Eye Study (BMES) reported an increased risk of early AMD associated with BMI outside the normal range.…”
Section: Body Mass Index and Markers Of Obesitymentioning
confidence: 99%
See 3 more Smart Citations